Dasar-Dasar Penyuluhan Islam - AS, Enjang (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2009)
One of daâwah form that cant forgotten its function for people development called Islamic counselling( irsyad ). The practice of this daâwah form need to be done with professionals manner, because in fact although task of frequent counselling entrusted with prominent of religion, but then if look to development goals attainment therefore that professionalism charge still has continually be built andÂ developed. At least, thereÂ are threeÂ available unsure that important to be made as counselling basic: (1 ) People have to know what do be passed on extension agents, (2 ) People have to know why such a that something, and (3 ) people have to want and able to do that something.